'And Since I Knew About the Possibilities There …': The Role of Open Creative Labs in User Innovation Processes. (10th February 2019) - Brinks, Verena
Abstract: Open spaces for experimentation and innovation are receiving growing attention from economic geography and beyond. They are discussed as new material settings for temporarily working on projects and ideas. Moreover, individual users are increasingly regarded as potential innovators who might benefit from "Open Creative Labs" and the (shared) resources provided there. This paper situates Open Creative Labs within the research strands of user innovation and the geography of knowledge creation and explores how Open Creative Labs have been used in four specific user innovation processes. On the basis of innovation biographies, it is reconstructed how Open Creative Labs concretely influenced the pathways of innovation. In all innovation processes, Open Creative Labs have been resources of innovation. In two cases, they can also be regarded as their local sources.